Final Semester Students' Perception of Difficulties in Solving Proof Problems in Real Analysis Course - Sri Susilawati Abdullah; I Ikrimah; Rosdiana IM (Manunggal Halim Jaya, 2026)
The Real Analysis course is a core course that emphasizes mathematical proof skills as indicators of students' deductive thinking. However, various findings show that proving is still a major difficulty, including for final-semester students. This study aims to describe the perceptions of final-semester students regarding the difficulties in solving proof problems in a Real Analysis course. This study used a descriptive qualitative approach with subjects being final-semester students of the Mathematics Education Study Program who had taken the Real Analysis course. Data were analyzed using thematic analysis and triangulation techniques to ensure data validity. The results show that students perceive difficulties in proving, especially in the stages of determining the initial steps of the proof, using formal definitions, and arranging a logical and systematic proof flow. In addition, negative perceptions of mathematical proof and procedural learning experiences reinforce these difficulties. This study concludes that difficulties in proving in Real Analysis courses are multidimensional, encompassing conceptual, structural, and affective aspects. These findings are expected to serve as a basis for developing Real Analysis learning strategies that are more focused on the proof process and students' needs.